Aportes académicos de un estudio exploratorio. La experiencia del trabajo de campo (2011)
ABSTRACT: Experience, work field access correct and incorrect choices, participant’s selection and the application of the interview technique are reported. Theoretical, methodological and ethical reflection of the exploratory study experience, generates meaningful learnings for the development of qualitative research practice, as well as showing aspects that in theory researchers’ are not able to see, even more if they are new.